2013
DOI: 10.1111/jtxs.12052
|View full text |Cite
|
Sign up to set email alerts
|

Gelation Behavior and Rheological Properties of Salt‐ or Acid‐Induced Soy Proteins Soft Tofu‐Type Gels

Abstract: Oscillatory tests data were analyzed using the power law and the weak gel models. Acid‐induced gels had higher storage modulus (G′) than salt‐induced gels. During gelation, both moduli increased gradually but never reached a steady state, with G′ being higher than G″. Under applied parameters, salt‐induced gels made from soybean coagulated faster than the ones made from soy protein isolate (SPI). Syneresis rate in salt‐induced gels was significantly lower than in acid‐induced gels, with SPI acid‐induced gel ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…The current study shows a significant (p < 0.05) difference in the textural characteristics of tofu produced with different coagulants. Hardness was higher for acidinduced gels than salt-induced gels, with values varying between 173 and 302 g. A similar tendency for hardness was observed by Murekatete et al [3] but was not in agreement with findings of Hou et al [31], who observed that salt-induced gels were the hardest. The higher the force required in breaking the tofu, the less brittle the tofu is [32].…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…The current study shows a significant (p < 0.05) difference in the textural characteristics of tofu produced with different coagulants. Hardness was higher for acidinduced gels than salt-induced gels, with values varying between 173 and 302 g. A similar tendency for hardness was observed by Murekatete et al [3] but was not in agreement with findings of Hou et al [31], who observed that salt-induced gels were the hardest. The higher the force required in breaking the tofu, the less brittle the tofu is [32].…”
Section: Resultssupporting
confidence: 68%
“…Gels made from soybean had L* values of 79.743 and 80.847 while the ones made from SPI had L* values of 75.093 and 76.147. This could be explained by the fact that first, soymilk has a more whitish color than SPI solution due its higher lipids content and second gels made from soybean have a more uniform and denser network with smaller network pore size than the ones made from SPI [3], resulting in higher luminosity, thus higher ability to emit or reflect light. In addition, knowing that in terms of lightness L* ¼ 100 represent the white color while L* ¼ 0 represent the black one, we could conclude that gels made from soybean were lighter than the ones made from SPI.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations